Barriers, facilitators and interventions to support help‐seeking amongst young people living in families impacted by parental mental illness: A systematized review. Issue 5 (12th July 2021) - Davies, Grace; P. Deane, Frank; Williams, Virginia; Giles, Chris
Abstract: Aim: Children living in families impacted by parental mental illness are at increased risk of adverse mental and physical health outcomes compared with children living in families unaffected by mental illness. Considered to be a hard‐to reach group, it is likely that there are unique barriers for these young people in seeking help for their difficulties. This systematized review synthesizes what is currently known about help‐seeking barriers, facilitators and interventions for young people affected by parental mental illness. Methods: Three databases were searched, yielding 2556 results and three studies were identified through other sources. Studies were screened on title and abstract review and were excluded if they were published before 2005 or if they did not include the perspectives of young people. At a second stage, full‐text articles were screened based on the inclusion criteria. Eleven studies were included for data extraction and quality appraisal. Results: Qualitative and quantitative data synthesis revealed three significant barriers (i) stigma, (ii) family communication and (iii) lack of belonging and shared experience, three key facilitators (i) individual characteristics, (ii) group identification and (iii) anonymity and three primary components of therapeutic interventions (i) psychoeducation, (ii) connection with peers and (iii) accessibility . Conclusions: It was found that stigma towards mental illness is highly salient amongst young people impacted by parental mental illness and has unique effects on their patterns of help‐seeking. Help‐seeking research amongst this group is still emerging, with a need for greater clarity in operationalisation of help‐seeking constructs and more robust methodological designs.